Urinary tract infection among the outpatients of a diagnostic center in Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2021)
Urinary tract infection (UTI) is one of the common bacterial infections occurring in the community and in hospitals of Bangladesh. A total of 300 urine samples were tested for UTI among which 100 were from children (age 1-15 years), 100 from adult female (16-75 years) and 100 from adult male (16-75 years). Out of 300, 126 samples were found positive for UTI (42%). The highest prevalence was observed among adult female (64%) followed by male and children (31% each). According to age groups, the highest prevalence was observed in female aged 16-35 years (70.73%) followed by female of 36-55 years (62.5%) and 56-75 years (52.63%). The highest prevalence for children was observed in age group 11-15 years (33.33%) and for adult male, it was 16-35 years (34.88%). The highest prevalence for adult female and male was observed in summer (66.67% and 38% respectively). The current study confirmed that Bangladeshi women and children are more vulnerable to UTI than Bangladeshi men. Regardless of age, women were more prone to UTI and the prevalence was highest in summer.Bangladesh J. Zool. 48(2): 347-356, 2020